2020
DOI: 10.1016/j.molcel.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Mechanisms of a Molecular RNA Polymerase/Chaperone Machine Required for Ribosome Biosynthesis

Abstract: Bacterial ribosomal RNAs are synthesized by a dedicated, conserved transcription-elongation complex that transcribes at high rates, shields RNA polymerase from premature termination, and supports co-transcriptional RNA folding, modification, processing, and ribosomal subunit assembly by presently unknown mechanisms. We have determined cryo-electron microscopy structures of complete Escherichia coli ribosomal RNA transcription elongation complexes, comprising RNA polymerase; DNA; RNA bearing an N-utilizationsit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 68 publications
1
79
0
Order By: Relevance
“…Protection of the phage λ early genes and E. coli rRNA operons (rrn) from Rho is conferred by multicomponent TACs. Recently solved cryo-EM structures of these TACs (Figure 6) revealed common and unique details of their action (Krupp et al, 2019;Huang et al, 2020). Both complexes assemble on boxA and boxB elements in the nascent RNA and share a set of NusABEG factors.…”
Section: Nusg-assisted Antiterminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Protection of the phage λ early genes and E. coli rRNA operons (rrn) from Rho is conferred by multicomponent TACs. Recently solved cryo-EM structures of these TACs (Figure 6) revealed common and unique details of their action (Krupp et al, 2019;Huang et al, 2020). Both complexes assemble on boxA and boxB elements in the nascent RNA and share a set of NusABEG factors.…”
Section: Nusg-assisted Antiterminationmentioning
confidence: 99%
“…Although the rrn-TAC has a different protein composition, analogous structural changes inhibit backtracking and NusAstabilized hairpin pausing and sequester NusG from Rho, with a much larger, well-folded SuhB dimer playing a central role in restructuring of the TAC components instead of λN (Singh et al, 2016). Notably, in addition to promoting pause-and termination-free RNA synthesis, the rrn-TAC acts as a molecular chaperone that actively assists the folding and maturation of the nascent RNA (Huang et al, 2020). Similarly to the ribosomeassociated chaperones, SuhB, S4 and Nus factors assemble into a ring around the RNA exit channel, extending the channel outward to accommodate a longer segment of the exiting RNA.…”
Section: Nusg-assisted Antiterminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nus complex formation begins with sequence-specific association of NusB/E with a short RNA element known as “BoxA”. Association of the Nus complex with both RNAP and the BoxA leads to formation of a loop in the nascent RNA (Bubunenko et al, 2012; Burmann et al, 2010; Huang et al, 2020; Singh et al, 2016). The most recently identified member of the Nus complex, SuhB, is recruited to elongating RNAP in a boxA -dependent manner (Singh et al, 2016), interacts with NusA, NusG, RNAP, and the nascent RNA, and is required for assembly and activity of the Nus factor complex (Dudenhoeffer et al, 2019; Huang et al, 2020, 2019; Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Association of the Nus complex with both RNAP and the BoxA leads to formation of a loop in the nascent RNA (Bubunenko et al, 2012; Burmann et al, 2010; Huang et al, 2020; Singh et al, 2016). The most recently identified member of the Nus complex, SuhB, is recruited to elongating RNAP in a boxA -dependent manner (Singh et al, 2016), interacts with NusA, NusG, RNAP, and the nascent RNA, and is required for assembly and activity of the Nus factor complex (Dudenhoeffer et al, 2019; Huang et al, 2020, 2019; Wang et al, 2007). The Nus factor complex prevents Rho termination (Squires et al, 1993; Torres et al, 2004) in a BoxA-dependent manner (Aksoy et al, 1984; Li et al, 1984; Squires et al, 1993), and BoxA elements are found in phylogenetically diverse copies of rRNA (Arnvig et al, 2008; Sen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%